The Origin of the Non-Governmental Sector in Russia during the Presidencies of Boris Yeltsin and Vladimir Putin (1991–2008) - Jach, Anna (The Copernicus Journal of Political Studies, 2018)
Apart from the public (first) and business (second) sectors, the third sector is one of the pillars constituting the modern democratic society. All the social interests are concentrated within the third sector and they are being implemented by the numerous non-governmental organizations cooperating with the state as well as business world. The birth of the third sector in Russia can be associated with the beginning of Mikhail Gorbachev reforms called the perestroika. The mental changes that the Russian society underwent influenced by the policy of glasnost led to the origin of public involvement into the social and political life, taking upon the role of the often ineffective state. The degree to which the citizens were involved in the activity of the NGOs was first of all associated with their quality of life and it depended on the attitude of the decision-makers towards the idea of social organizations. The time of Boris Yeltsin presidency was characterized by two phenomena: a drop in the standard of living accompanied by the intensification of criminalization within the public life and the positive attitude towards the introduction of the third sector. After the new president assumed the post, the approach of the new authority changed in a negative way and the politics implemented led to gaining full control over public associations. The so-called liberalization of the law in respect to the third sector was only a display of Kremlin’s political will and did not signify serious treatment of the principles of the democratic and civic society. The third sector, one of the pillars supporting the civil society is at present in the state of consolidation, dealing with numerous amendments of legal norms. After the period of mimicking western solutions, the Russian NGOs became a power that must be taken into account by the Russian decision-makers. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762